A survey on the current status of gynecological and breast diseases among 13 031 women in Pudong New Area, Shanghai in 2023 - LI Lu; ZHAO Xichang; ZHANG Yuwei; YE Yufang (Shanghai yufang yixue)
ObjectiveTo investigate the prevalence of gynecological and breast diseases among retired or economically disadvantaged women in part of Pudong New Area of Shanghai under the policy support of screening gynecological diseases and breast diseases for retired and women with economic difficulties in life in Shanghai, to analyze the characteristics of these diseases, so as to provide a scientific basis for the improvement of relevant prevention and treatment strategies.MethodsBased on the gynecological census data of 13 031 cases in five towns, including Xinchang Town, Xuanqiao Town, Laogang Town, Wanxiang Town and Shuyuan Town, conducted by Shanghai Pudong Hospital in 2023, descriptive analysis methods were used to explore the prevalence and age characteristics of common gynecological and breast diseases.ResultsThe total detection rate of gynecological and breast diseases among women in the screening area in this study was 68.29%, with uterine fibroid (22.35%), sarcoidosis of the breast (17.06%), cervicitis (15.37%), vaginitis (8.39%) and ovarian cyst (2.61%) ranking the top 5 in the detection rate among the screening population. The differences of the detection rates in the four major diseases [uterine fibroid (χ2=233.217, P<0.001), breast nodules(χ2=169.896, P<0.001), cervicitis (χ2=388.683, P<0.001), and ovarian cysts (χ2=72.298, P<0.001)] by different age groups were statistically significant (P<0.05) . Moreover, the results of pairwise comparison of different age groups showed that the detection rates in the age group under 45 years old and 45‒55 years old were higher than that in the age group of 55‒65 years old and over 65 years old.ConclusionThe detection rate of gynecological and breast diseases in the younger age group was higher, indicating a certain trend of younger onset of diseases. Uterine fibroid, sarcoidosis of the breast , and reproductive tract diseases such as cervicitis, vaginitis, and ovarian cyst are the main diseases affecting the research subjects. Therefore, medical institutions can combine routine work in screening diseases and carry out corresponding health education and health promotion activities for these key diseases to improve women’s health.